KORELASI ANTARA SELF – REGULATION DENGAN SINDROM FEAR OF MISSING OUT (FOMO) PADA MAHASISWI PROGRAM STUDI BIMBINGAN DAN KONSELING UNIVERSITAS IVET SEMARANG - Siti Aulin Niswa; Widya Novi Angga Dewi; YM Indarwati (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
This research aims to describe the correlation between Self-Regulation and Fear of Missing Out (FoMo) Syndrome in Female Students of the Guidance and Counseling Study Program at IVET University Semarang. This type of research is quantitative correlational research using two variables, namely self-regulation and FoMo syndrome. The sample used in this research was 34 female students in the 5th semester of the 2021/2022 class. The technique used in sampling in this research was purposive sampling technique. Data collection was carried out using the selfregulation and FoMo syndrome scales. The results obtained using the product moment correlation technique (Γxy) = - 0.453 and p = 0.007 (p < 0.05). This means that there is a negative relationship between self-regulation and FoMo syndrome in female students. According to the results of the data that has been obtained, the variable self - regulation (. Meanwhile, the FoMo syndrome variable has a hypothetical value = 50 and an empirical mean = 55.29. This means that the data shows that the FoMo syndrome of female students is relatively high because it has a hypothetical mean value < the empirical mean. So it can be concluded that the lower the self-regulation that female students have, the higher the FoMo syndrome that occurs. So it can be concluded that the hypothesis formulated in this research is accepted.